Actinobacillus pleuropneumoniae: a review of an economically important pathogen. (2nd November 2020) - Gale, Christina; Velazquez, Eduardo
Abstract : Actinobacillus pleuropneumoniae is one of the causative agents of porcine pleuropneumonia, which is an economically important respiratory disease of pig production. Clinical signs vary based on the severity of disease and lung lesions present, but include fever and severe respiratory signs including coughing and laboured breathing. Numerous serotypes exist which vary in their virulence, and virulence of serotypes has also been shown to be vary between countries. It is important to establish which serotypes are present and active on a farm as well as carrying out seroprofiling to determine the correct time for implementation of control measures such as vaccination. Understanding of transmission routes is vital, including the role of carrier animals on the farm which are persistently infected and can shed the bacteria, therefore infecting other animals. Therefore, as with all infectious diseases, good standards of internal and external biosecurity are important in controlling the disease on farm. Vaccination has been shown to be effective on affected farms in preventing outbreaks, reducing clinical signs if they occur, and most important to the farmer, preventing losses in mortality, feed conversion ratio and growth. Therefore, vaccines are often a good choice for controlling pleuropneumonia on farm and reducing the need for treatment using antimicrobials.